PURA TAMAN LINGSAR, DALAM MEMBANGUN KOHESI SOSIAL ANTARA ISLAM WETU TELU ETNIS SASAK DENGAN KOMUNITAS HINDU ETNIS BALI DI LOMBOK - Sumertha, I Wayan (Widya Sandhi, 2019)
The Indonesian nation, also dubbed the Pluralistic nation, because various major religions exist in Indonesia such as: Islam, Protestant Christianity, Catholic Christianity, Hinduism, Buddhism and Kong Hut Chu as well as the Original Archipelago religion still survive. Referring to this phenomenon, this seems to underlie the founders of the Indonesian nation to formulate the Pancasila and the 1945 Constitution as the State of the Republic of Indonesia. As a nation that has diversity, with a variety of ethnicities, religions, cultures, and customs, besides being an attraction due to its uniqueness and specificity, distinguish it from other nations in the World. Strengthening politics Identity is expressed through various forms of representation that are recognized by others and themselves. This condition holds the seeds of conflict quite high and easily ridden by other interests that are contrary to the life of the nation and state under the ideology of Pancasila and the 1945 Constitution. These problems can only be anticipated through increased fostering of harmony, and instilling awareness of the diversity of the nation and a country that is always carried out by all components of the Indonesian nation. On the island of Lombok there is a monumental symbol of the size and harmony of life between religious communities, namely between the Balinese Hindu Community and the Sasak Wetu Telu Islamic Community. The monument is Pura Lingsar, which until now still exists to function as a medium to increase social and religious social interaction of both ethnicities and religions on Lombok Island.